ANALISIS KESALAHAN SINTAKSIS DALAM TEKS WACANA TULIS KARYA MAHASISWA ANGKATAN 2019 JURUSAN BAHASA DAN SASTRA MANDARIN UNESA - Ibrizah, Falikhatul; Subandi, Subandi (Jurnal Bahasa Mandarin, 2020)
ABSTRAK Dalam menulis teks wacana tulis, mahasiswa angkatan 2019 jurusan Bahasa dan sastra Mandarin Unesa sering kali melakukan kesalahan. Salah satu kesalahan yang cukup sering ditemukan dalam teks wacana tulis adalah kesalahan pada tataran sintaksis yang merupakan data dalam penelitian ini. Penelitian ini bertujuan untuk mengidentifikasi bentuk kesalahan sintaksis yang dilakukan mahasiswa dan mengetahui penyebab terjadinya kesalahan sintaksis dalam teks wacana tulis. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif, karena penelitian ini bertujuan untuk mendeskripsikan bentuk kesalahan sintaksis yang ditemukan pada teks wacana tulis yang disusun oleh mahasiswa dan mendeskripsikan faktor penyebab kesalahan sintaksis yang dilakukan mahasiswa. Teknik pengumpulan data dalam penelitian ini menggunakan teknik simak bebas libat cakap (SBLC) dan teknik catat. Teknik analisis data menggunakan teknik analisis metode agih. Berdasarkan hasil pembahasan mengenai kesalahan sintaksis pada teks wacana tulis karya mahasiswa. Kesalahan-kesalahan tersebut diklasifikasikan berdasarkan taksonomi siasat permukaan yaitu (1) Penghilangan (Omission errors ) ditemukan 3 bentuk kesalahan yaitu penghilangan unsur pembentuk frasa, penghilangan kata kerja dan penghilangan unsur pembentuk pada kalimat. (2) Penambahan (Addition errors ) ditemukan 2 bentuk kesalahan yaitu penambahan unsur pada frasa dan penambahan unsur pada kalimat. (3) Salah formasi (Misformation errors) ditemukan 1 bentuk kesalahan yaitu posisi kata bantu bilangan yang tidak tepat (4) Salah susun (Misordering errors ) ditemukan 3 bentuk kesalahan yaitu posisi unsur superlatif yang tidak tepat, posisi struktur kalimat yang kurang tepat dan kesalahan pada susunan gramatikal. (5) Penghilangan (omission errors) dan Salah susun (Misordering errors) ditemukan 1 bentuk kesalahan yaitu kesalahan posisi unsur klausa. Dari hasil penelitian dapat disimpulkan bahwa faktor yang menyebabkan terjadinya kesalahan sintaksis pada teks wacana tulis yang disusun oleh mahasiswa angkatan 2019 adalah karena faktor interferensi bahasa ibu mahasiswa, faktor kekurangpahaman mahasiswa terhadap penggunaan kata dalam bahasa Mandarin dan kekurangpahaman mahasiswa terkait kaidah-kaidah sintaksis bahasa Mandarin. Kata kunci : Kesalahan Sintaksis, Teks wacana tulis, Bahasa Mandarin ABSTRACT In writing written discourse texts, students of the 2019 batch of Unesa Mandarin Language and Literature majors often make mistakes. One of the errors that are quite often found in written discourse texts is an error at the syntactic level which is the data in this study. This study aims to identify the form of syntactic errors made by students and find out the causes of syntactic errors in written discourse texts. The approach used in this study is a qualitative descriptive approach, because this study aims to describe the form of syntactic errors found in written discourse texts compiled by students and describe the factors causing syntactic errors made by students. The data collection technique in this study used the free-involvement-free listening (SBLC) technique and note-taking technique. The data analysis technique used the analysis technique of the agih method. Based on the results of the discussion about syntactic errors in the text of written discourse by students. These errors are classified based on the taxonomy of surface tactics, namely (1) Omission errors, found 3 forms of errors, namely omission of phrases forming elements, omission of verbs and omission of forming elements in sentences. (2) Addition errors found 2 forms of errors, namely adding elements to phrases and adding elements to sentences. (3) Misformation errors found 1 form of error, namely the position of the auxiliary number that is not right (4) Misordering errors found 3 forms of error, namely the position of the superlative element that is not right, the position of the sentence structure is not right and errors in grammatical order. (5) Omission errors and Misordering errors found one form of error, namely the error in the position of the clause element. From the results of the study, it can be concluded that the factors that cause syntactic <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAJkAAAABCAYAAADNaQyUAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAAB1tXAAASFwAHW1cAABIXAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAJmgAwAEAAAAAQAAAAEAAAAAVSZn3wAAAAlwSFlzAAAQAwAAEAMBPCQIdwAAABlJREFUKBVjZEk6UMUwCkZDgEYhwPj/314A6eEEXTBIgZgAAAAASUVORK5CYII=" alt="page1image47448832" width="152.450000" height="0.480000"> <img src="data:image/png;base64,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" alt="page1image37201872" width="467.900000" height="467.900000"> <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAF4AAAABCAYAAABXChlMAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAABFexAAAKpgAEV7EAAAqmAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAF6gAwAEAAAAAQAAAAEAAAAAV+nrgQAAAAlwSFlzAAAQDgAAEA4BNRRl5AAAABdJREFUGBljZEk6UMUwCugaAn9+fJkOAGwXBSGSqWFjAAAAAElFTkSuQmCC" alt="page1image47449024" width="93.144000" height="0.480000"> 1 ANALISIS KESALAHAN SINTAKSIS DALAM TEKS WACANA TULIS BAHASA MANDARIN errors in written discourse texts compiled by 2019 class students are due to the interference factor of the students’ mother tongue, the student’s lack of understanding of the use of words in Mandarin and students’ lack of understanding regarding the syntactic rules of Mandarin. Keywords: syntax error, writing discourse texts, Chinese language